Engineering Power Attributions in Conversational Agents - The Unexplored Impact of Vocal Vibrato and Vocal Tract Length - Fotis Efthymiou (Marketing Review St.Gallen, 2021)
This work provides evidence for designing perceived power-related personality traits of conversational agents based on vocal features. The vocal vibrato and the vocal tract length of a female and a male humanlike voice, respectively, were systematically manipulated to derive recommendations for voice engineering.
Keywords: 650